The use of flashcard to improve students' vocabulary mastery in writing descriptive text: case of grades 7 of SMPN 5 Ambarawa in the academic year 2021/2022 - Alifvia Putri Azharra; Jafar Shodiq; Arso Setyaji (Universitas Islam Malang, 2022)
This study aims to determine: (1) To find out students' vocabulary mastery of SMPN 5 Ambarawa in writing descriptive text taught with using flashcard (2) To find out students' vocabulary mastery of SMPN 5 Ambarawa in writing descriptive text taught without using flashcard. (3) To know the significant difference of students' vocabulary mastery in writing descriptive text taught with and without using flashcard. This research is a quasi-experimental research. This research was conducted at SMPN 5 Ambarawa in May-June 2022. The population in this study was class VII students consisting of 33 students in the experimental class and 33 students in the control class. The experimental class in its treatment using flashcards while the control class only uses the lecture method as a learning process. The design used in this study is the Pre-Test Post-Test Control Group Design. The research instrument was in the form of a learning outcome test. To test the hypothesis using the paired sample t-test. Data analysis was done descriptively. The results of this study indicate that: (1) in the experimental class the average value of the pretest is 57.33 while the posttest average value is 82.64 which is higher than the control class, (2) in the control class the average value of the pretest is 56.06 while the posttest average value is 66.66, still lower than the experimental class (3) the average posttest value of the experimental class > control class is 82.64 > 66.67 which means that the vocabulary mastery of the experimental class is higher than the control class. In the paired t-test, the results obtained are sig.2 tailed of 0.000 <0.05 using flashcards is more effective.